PERCEPTION OF DISABILITY IN PRESCHOOL CHILDREN THROUGH VISUAL METHODS - Barbora Kováčová (Theoretical Hypotheses and Empirical Results, 2026)
The study describes ways in which selected disabilities can be presented to kindergarten children in a comprehensible and age-appropriate manner. It presents research findings in which children in kindergartens were asked to describe picture cards depicting various forms of disability. This approach makes it possible to capture children’s natural interpretations and spontaneous reactions to visual stimuli. At the same time, it provides space for identifying misconceptions, inaccuracies, or simplified explanations that young children tend to construct. The results highlight the importance of visual methods in developing understanding and acceptance of diversity within peer groups. The knowledge obtained in this way can be used in the design of inclusive educational activities in pre-primary education.